Sistemática de Chalcis Fabricius (Hymenoptera: Chalcididae) - Saguiah, Pâmella Machado. (2019)
Chalcidinae is the second largest subfamily of Chalcididae, comprising about 760 species with world wide distribution. The subfamily comprises three tribes, among them the Chalcidini species, with six genera and approximately 350 species with higher diversity occurs in the neotropical region. Chalcis is the type genus of the tribe and currently has 60 recognized species. It is distributed worldwide and its higher diversity is concentrated in temperate regions of the northern hemisphere. Some species are known to be egg-pupal or larval-pupal parasitoids of aquatic Stratiomyidae (Diptera). Taxonomic revisions are known for the fauna of the New World, Europe, Russia and Oriental region. In 1992, two groups of species were proposed for Chalcis, based on the length of the female hypopygium and a phylogeny for tribe where Chalcis was represented as a terminal taxon of the tree. The results of this analysis indicated 10 apomorphs for the genus and Melanosmicra Ashmead was recognized as its sister group. A new phylogeny was introduced in 1997, although it is at the family level. The results of the analyses were inconclusive as to the positioning of Chalcis in Chalcidini. The infrageneric phylogenetic relationship to the genus has not been studied in either of the two previous analyzes and the evolutionary history of the genus is hitherto unknown. The objective of this work was: 1) To investigate the monophyly of Chalcis and the phylogenetic relationship between the species and among the other genera of Chalcidini; 2) To review the fauna of South America, poorly sampled fauna that, until the present moment, only has a single species known for the region, Chalcis pilicauda (Cameron). Phylogenetic analyses with morphological, molecular and combined data are presented and the monophyly of the genus was strongly supported in most analyses. Two main lineages occur within the genus, corresponding to the groups of species previously proposed. A new generic delimitation is proposed based on the results obtained in the phylogenetic analyzes presented here. For the study of South American fauna, six species not described and a synonymy associated with Chalcis pilicauda was reviewed, revalidating the species C. ornatifrons (Cameron). Six new species descriptions and an identification key for the South American species are presented.